若√2^(m+n-2)和√3^(3m-2n+2)都是最简二次根式,则m=?n=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 16:38:57
若√2^(m+n-2)和√3^(3m-2n+2)都是最简二次根式,则m=?n=?若√2^(m+n-2)和√3^(3m-2n+2)都是最简二次根式,则m=?n=?若√2^(m+n-2)和√3^(3m-2
若√2^(m+n-2)和√3^(3m-2n+2)都是最简二次根式,则m=?n=?
若√2^(m+n-2)和√3^(3m-2n+2)都是最简二次根式,则m=?n=?
若√2^(m+n-2)和√3^(3m-2n+2)都是最简二次根式,则m=?n=?
m+n-2=1
3m-2n+2=1
解得m=1,n=2
若√2^(m+n-2)和√3^(3m-2n+2)都是最简二次根式,则m=?n=?
如果m和n互为相反数,则m+2m+3m+4m+5m+5n+4n+3n+2n+n=
[(m-n)^2*(m-n)^3]^2/(m-n)^4
[(m-n)^2*(m-n)^3]^2/(m-n)^4
3m(m-n)-2n(m-n)的平方
因式分解(n-m)^3(m-n)^2-(m-n)^5
(m-n)2(n-m)3(n-m)4化简
(n-m)^3×(m-n)^2-(m-n)^5
计算(m+n)^3-(n+m)(m-n)^2
(m-n)^3(n-m)^2(m-n)=_____
4m(m-n)^2+4n(n-m)^3
已知m>0,n>0,且m≠n.化简:3m/(2m+根号mn)×[(根号m^3-根号n^3)/(m-根号mn)-(m-n)已知m>0,n>0,且m≠n.化简:3m/(2m+√mn)×[(√m^3-√n^3)/(m-√mn)-(m-n)]
2m-3n-m+2n
(m-n)3-(2n-m)3
(3m-n)(m-2n)=()
(m+2n)(m-3n)
(m-3n)(2m+n)
约分(m-n)^2/(n-m)^3